IMPLEMENTATION OF DISCOVERY LEARNING MODEL TO IMPROVE STUDENT'S LEARNING OUTCOMES MECHANICAL WAVES IN CLASS XI MIPA 2 SMA NEGERI 1 MOJOSARI MOJOKERTO - Hermawan Hermawan (Sean Institute, 2022)
Specifically, based on initial observations and reflections, it was obtained an illustration that class XI MIPA 2 SMA Negeri 1 Mojosari was a class with low learning motivation. In this class students tend to pay less attention to lessons, the learning outcomes obtained also do not meet the Minimum Completeness Criteria (KKM). The test results for the previous material completeness only reached 66.67% or only 22 out of 33 students completed it. Based on this, research was carried out with the aim of knowing the increase in student learning outcomes in mechanical wave material through learning models discovery learning at SMA Negeri 1 Mojosari Mojokerto Class XI MIPA 2 semester 2 of the 2018/2019 academic year. This research is a classroom action research conducted from January to February 2019 involving 33 students of class XI MIPA 2 for the 2018/2019 academic year. This research was conducted for two cycles, each cycle consisting of 4 (four) stages, namely planning, implementing, observing, and reflecting. Based on the results of research and reflection, it can be concluded that the implementation of the discovery learning learning model more effective. The implementation of the discovery learning learning model can also improve and complete student learning outcomes, this is evidenced by the increase in classical completeness from 84.85% in the first cycle to 90.9% in the second cycle . In addition, through the discovery learning learning model, student activities become more active, and are able to familiarize scientific behavior